Design of fuzzy logic controlled zero voltage switching based interleaved high gain converter - M.V. Sudarsan; Ch. Sai Babu; S. Satyanarayana (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
The conversion of low level DC voltage to high level DC voltage at lower duty ratios with less ripple current at source side is a challenging task in the distributed generation systems. Active switched inductor (ASL) converter is a high gain converter and has a large amount of input ripple current due to the parallel charging of the inductors during on time of the switches and series discharge of the inductors during off time of the switches. This large input ripple current in the converter when used in distributed generation (DG) affects the life time of low voltage batteries and fuel cells, the efficiency of photovoltaic source, increases the size and losses in the filtering stages and decreases the power density of the converters. In this paper, soft switching of interleaved active switched inductor (IASL) through Zero Voltage Switching (ZVS) is designed to overcome the limitations of ASL. The performance is analyzed in terms of its gain, input current ripple, switching loss and efficiency. An M-type resonant switch is used to achieve soft switching through ZVS technique.A proper value of resonant elements (inductor and Capacitor) is designed to achieve ZVS to improve the efficiency. Regulated voltage of proposed converter is required in DG systems and is possible with closed loop control. Fuzzy Logic controller (FLC) is designed to regulate the voltage and its dynamic performance is analyzed for different load values and also for sudden changes in load. Hardware model of the proposed ZVS based IASL converter with FLC is implemented and the results are verified with simulation results obtained from MATLAB Simulink.